Radvâ 'Âşûr ve Sülasiyyetü Gırnâta adlı eserinde göç teması - Özdemir, Mediha Büşra (My University, 2017)
Hakikati hayalle zenginleştirerek edebiyat alanına dahil eden tarihî roman; Walter Scott’tan günümüze kadar birçok merhaleler geçirmiş ve bulunduğu olgunluğa erişmesi iki yüz yılı bulmuştur.

A historical novel that enriches the truth with imagination and incorporated into the field of literature has spent many steps from Walter Scott to present day and it has taken two hundred years to reach the maturity it is in.
Keywords: 20. yy; Arabic Language; Arap Dili; Arap dili ve edebiyatı; Göç, Edebiyatta; Historical Novel; Modern Arabic Literature; Modern Arap Edebiyatı; Radvâ ‘Âşûr; Radwa Ashour; Roman; Sülasiyyetü Gırnâta; Tarihî Roman; Tarihi roman, Arap; The Granada Trilogy